1975
DOI: 10.1246/cl.1975.259
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Reduction of Aromatic Nitro Compounds With Hydrazine in the Presence of Iron(iii) Chloride and Active Carbon

Abstract: A catalytic reduction of aromatic nitro compounds to aromatic amino compounds with hydrazine in the presence of Fe(III) chloride and active carbon was studied. The corresponding amino compounds were obtained with excellent purities and in good yields. The method was also applied to the partial reduction of dinitro compounds.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
19
0
1

Year Published

1996
1996
2014
2014

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(20 citation statements)
references
References 0 publications
0
19
0
1
Order By: Relevance
“…34 An analogous compound 2 and model compounds 3 -7 were also synthesized from 0.005 mol of respective amino compounds: 1.64 g of 3¢-methyl-4¢-aminobenzo-15-crown-5 [35][36][37] (2), the 0.30 g of propylamine (3), the 0.47 g of aniline (4), the 0.66 g of 2-anisidine (5), the 0.66 g of 4-anisidine (6), and the 0.77 g of 2,4-dimethoxyaniline (7).…”
Section: Methodsmentioning
confidence: 99%
“…34 An analogous compound 2 and model compounds 3 -7 were also synthesized from 0.005 mol of respective amino compounds: 1.64 g of 3¢-methyl-4¢-aminobenzo-15-crown-5 [35][36][37] (2), the 0.30 g of propylamine (3), the 0.47 g of aniline (4), the 0.66 g of 2-anisidine (5), the 0.66 g of 4-anisidine (6), and the 0.77 g of 2,4-dimethoxyaniline (7).…”
Section: Methodsmentioning
confidence: 99%
“…The reduction has also been reported on carbon activated with FeCl 3 or by the presence of nitrate ion. 167,171 Oxidized carbons have also been used as catalysts and the reported yields are lower than those obtained with graphite. 168 More recent reports showed that the reduction of nitroaromatic compounds by hydrazine is catalyzed by carbon blacks (e.g.…”
Section: Reduction Of Nitrobenzene By Hydrazinementioning
confidence: 99%
“…A few workers examined the reduction of aromatic nitro compounds to corresponding aniline over activated carbon or graphite in the presence of iron chloride [9,10]. Good yields of aniline products (> 90%) were obtained for several nitro substrates.…”
Section: Introductionmentioning
confidence: 99%